Post-covid-19 consumers need for social connections: How lockdown strictness influence consumers’ behavioral intentions of buying in physical stores - Pinto, Maria Madalena Guerra Cardoso (2023)
Dissertation presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Marketing Intelligence